Local and Internal Therapeutic Approach in the Management of Bhagna with special Emphasis to Micro-Trabecular Fractures of the Humerus Head to avert the Intended Surgery (International Journal of Ayurveda and Pharma Research, 2023)
Sports have become more and more popular in our country, which has led to an increase in traumatic injuries whose aetiology is linked to sports injuries. When he described Bhagna Chikitsa (management of fractures), the renowned Acharya Sushruta properly identified injuries, signs and symptoms, local and internal therapies, disorders related to bones, and optimal bone healing features. Acharya Sushruta developed the fundamental principles of Bhagnasthapna (reduction of fractures), Sthirikarna (stabilisation), Anchana (traction), Bandhana (splints), Lepa (pargeting), and Parisheka (douching) in order to treat these injuries while they are still active and to rehabilitate the joint to prevent subsequent problems like joint stiffness. Trauma management has a long history that extends back to the Vedic era and is still useful today. In an effort to avoid the desired surgery, the case report of a diagnosed case of Bhagna of a 25 year young male with special reference to the micro-trabecular fracture of the humerus head that follows, further discusses the Sushruta Samhita's all-encompassing approach to treating Bhagna by utilising internal drugs and local remedies. The treatment of micro-trabecular fractures only entails calcium supplements, NSAIDs, and later micro-bone grafting surgery. Purpose of Study: The key objective of the study is to effectively manage a post-traumatic micro-trabecular fracture of the humerus head refrain from performing the preferred micro-bone grafting surgery using local treatments and internal medications from the Sushruta Samhita. Observation and Conclusion: Within two days, the patient saw a considerable reduction in discomfort, and by the time the therapy was over, the patient was completely symptom-free, had no shoulder stiffness, and had experienced a large increase in the AROM (Active Range of Motion) of the shoulder joint.